2018
DOI: 10.1002/chem.201800322
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzo[a,e]pentalenophanes: Bending a Non‐Alternant Hydrocarbon

Abstract: In cyclophanes, an aromatic moiety is incorporated into a (strained) cyclic structure. Of particular interest as model systems for bent carbon nanostructures are those containing polycyclic aromatic hydrocarbons. Dibenzo[a,e]pentalene (DBP) is a non-alternant polycyclic hydrocarbon with small band gap and tunable optoelectronic properties. However, changing these properties by bending of the DBP structure has yet to be investigated. Herein, we report the synthesis, optoelectronic, and structural properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 73 publications
2
53
0
Order By: Relevance
“…The undesired strain‐relieving carbocation rearrangement might proceed in the oxidation of 20 e with DDQ . Thus, Esser's dehydrative aromatization method using the Burgess reagent [methyl N ‐(triethylammoniumsulfonyl)carbamate], in which no carbocations are formed, is advantageous for the aromatization of highly bent structures . As an alternative aromatization method for the highly bent dibenzo‐fused cyclohexadiene, the Diels–Alder reaction of 20 g with N ‐phenylmaleimide afforded the corresponding phenanthrene‐based cyclophane 23 as a single diastereomer (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The undesired strain‐relieving carbocation rearrangement might proceed in the oxidation of 20 e with DDQ . Thus, Esser's dehydrative aromatization method using the Burgess reagent [methyl N ‐(triethylammoniumsulfonyl)carbamate], in which no carbocations are formed, is advantageous for the aromatization of highly bent structures . As an alternative aromatization method for the highly bent dibenzo‐fused cyclohexadiene, the Diels–Alder reaction of 20 g with N ‐phenylmaleimide afforded the corresponding phenanthrene‐based cyclophane 23 as a single diastereomer (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in 2012, Bodwell reported the racemic synthesis of pyrene‐based chiral bent cyclophanes via the McMurry coupling followed by the VID (valence isomerization dehydrogenation) reaction, although the product yield was low (12 %) (Scheme b, middle) . In 2018, Esser reported the racemic synthesis of dibenzopentalene‐based chiral bent cyclophanes via the Suzuki–Miyaura cross‐coupling followed by arylation and dehydration reactions with improved product yields of 14–36 % (Scheme b, bottom) . However, in these examples, the optical resolution of racemates by chiral HPLC columns was required to obtain enantiopure cyclophanes …”
Section: Introductionmentioning
confidence: 99%
“…The enantioselective [2+2+2] cycloaddition of biphenyl‐linked internal 1,7‐diyne 1 a with 1,2‐dihydronaphthalene ( 2 a ) proceeded at 40 °C in the presence of a cationic rhodium(I)/( R )‐segphos complex (20 mol %) to give the desired chiral cyclohexadiene (+)‐ 3 aa in good yield with high ee value of 88 % (entry 1). Although the Diels–Alder reaction of (+)‐ 3 aa with benzyne did not proceed, that with 1,4‐naphthoquinone followed by reductive aromatization using LiAlH 4 and the Burgess reagent proceeded to give the desired triptycene precursor (+)‐ 4 aa in 30 % yield with complete diastereoselectivity. But unfortunately, the treatment of (+)‐ 4 aa with DDQ did not give the desired chiral triptycene (+)‐ 5 aa , instead, an unidentified complex mixture of products was generated…”
Section: Methodsmentioning
confidence: 99%
“…[6g] Because of this large distortion, there are concerns about the stability of 5.H erein, we have established that the appropriate introductiono fs ubstituents into the biphenyllinked 1,7-diyne 1 and 1,2-dihydronaphthalene (2a)r ealizes this concept.Scheme 2d isplays the enantioselective synthesis of chiral triptycene 5.T he enantioselective [2+ +2+ +2] cycloaddition of biphenyl-linked internal 1,7-diyne 1a with 1,2-dihydronaphthalene (2a)p roceeded at 40 8Ci nt he presence of ac ationic rho-Scheme1.Enantioselective synthesis of chiral triptycenes.[a] Y.Communication dium(I)/(R)-segphos complex (20 mol %) to give the desired chiral cyclohexadiene (+ +)-3aa in good yield with high ee value of 88 %( entry 1). Althought he Diels-Alder reactiono f( + +)-3aa with benzyne did not proceed, that with 1,4-naphthoquinone followed by reductive aromatization using LiAlH 4 andt he Burgess reagent [17] proceeded to give the desired triptycene precursor (+ +)-4aa in 30 %y ield with complete diastereoselectivity. But unfortunately,t he treatment of (+ +)-4aa with DDQ didn ot give the desired chiral triptycene (+ +)-5aa,i nstead, an unidentified complex mixture of products was generated.…”
mentioning
confidence: 99%
“…[33] We were able to obtain its anion radical 1C À À ,c ation radical 1C + + and dication 1 2 + + and investigatedt heir structural and electronic properties by X-ray crystallography,E PR spectroscopy and DFT calculations. With the synthesis of (2,7)dibenzo[a,e]pentalenophanes [33] (DBP-phanes) and DBP-based nanohoops [34][35][36] we recently showed that the DBP unit can be bent [37] without strongly alteringi ts optoelectronic properties. Hence, we herein performed ac hemical reduction of DBP-phane 2 (Figure 1C)t oi nvestigate the influence of bending.…”
Section: Introductionmentioning
confidence: 99%